ANALISIS MAJAS SINDIRAN PADA AKUN TIKTOK @sandradewi88__ - Ari Musdolifah; Andrea Prasetya; Elok Yulia Widayanti; Naila Dwi Maida Husniyyah; Sarah Gita Cahyarani; Talitha Iftitah Hendrawan (PT. CASA CENDEKIA MEDIA, 2024)
This research is based on the widespread use of satire in the comments column on social media in the community. This research was conducted using a qualitative method, data collection was carried out through the technique of listening and taking notes. There are many uses of language expressed in a style that is not good for people to use on social media. Social media is an application platform that can allow online communication. The use of satire in the comments column has the intention of bringing down the intended party. In the case experienced by Sandra Dewi's husband named Harvey Moise, there were many statements that were of a derogatory nature through the comments column on his personal social media which were expressed using satire. Satire is divided into several types such as irony, satire, cynicism, sarcasm, and innuendo.